Utilization of oil palm frond (OPF) as a partial replacement of sand in cement sand brick for non-load bearing structure - Ag Ku Afiq Ikhwan, Ag Jaafar (2019)
Cement Sand Brick is made from a mixture of cement and sand and widely used in construction industry. Rapid growing towards construction industry in Malaysia lead to high demand of sand in order to fulfil the construction materials required for many projects in one time. Therefore, Inadequate supervision and law enforcement in sand mining activities will increase the number of illegal sand mining activities that may cause water pollution, endangered the aquatic life, erosion of river bank and reducing the national sand reserve due to the uncontrolled amount of sand mining activities. At the same time the price of sand will increase due to the lack of supplies and the cost of imported sand from other country in order to fulfil the construction industry demand in a project. Hereby, some researches have been conducted to reduce the usage of sand in construction industry by replacing partial amount of sand with other suitable and organic materials. As Malaysia is one of the biggest oil palm industry in the world, a lot of agricultural waste are depleted including empty fruit branches(EFB), Oil Palm Shell(OPS), Oil Palm Trunk(OPT), Oil Palm Frond(OPF) and others which may contribute to pollution that can be used as an alternative to replace sand. By replacing sand partially with oil palm frond(OPF) sand mining and agricultural waste problem can be reduced as well as more economical and green friendly cement sand brick can be produced. This research aims to identify the suitability of oil palm frond(OPF) as a partial replacement of sand in brick manufacturing which act as sustainable non-load bearing construction material. The field of studies also cover the important parameters including compressive strength, flexural strength and water absorption. All specimens were subjected to water curing. The compression and flexural strength test has been conducted for 7,14 and 28 days after the bricks undergo water curing process and, water absorption test also conducted for 28 days after undergo water curing process and dried in the oven for 24 hours before it is being soak for another 24 hours. In terms of compressive strength, the higher the percentages of oil palm frond (OPF), the lower the compressive strength. In other hand, regarding to the flexural strength the higher the percentage of oil palm frond(OPF) the lower its flexural strength. In addition, water absorption test was conducted and found out that the higher the percentage of oil palm frond(OPF), the higher the water absorption. However, since the objective of this research is to find out the suitability of oil palm frond mix sand cement bricks to support non-load bearing structure, so it is applicable to use for non-load bearing application.